Special Considerations for Tympanoplasty Type I in the Oncological Pediatric Population: A Case-Control Study - Richard, Celine; Baker, Emily; Wood, Joshua (Frontiers in Surgery, 2022)
Introduction Although cutting-edges antineoplastic therapies increase survival in children with malignancies, the optimal surgical strategy to address associated comorbidities such as chronic tympanic membrane perforation is still poorly documented. The aim of this study is to evaluate the outcomes of type I tympanoplasty in pediatric cancer survivors who received chemo and/or radiotherapy to the skull and to identify potential associated risk factors. Methods This case-control study included medical records review of oncologic patients (age <21) treated at the same Academic medical oncologic center between March 2015 and July 2021 and referred for conductive hearing loss and chronic tympanic membrane perforation. Patients and middle ear status-related variables were analyzed, and outcomes were compared with matched peers without any history of malignancies. Results A total of seven pediatric cancer survivors and seven paired children without any history of malignancies were included in this report. The mean age at tympanoplasty type I surgery was 10.2 years (range = 4.3–19.9; median = 7.9 years) for the pediatric cancer survivors' group and 10.1 years (range = 5.5–19.2; median = 7.9 years) in the control group. Three pediatric cancer patients had received chemotherapy alone, one patient had radiotherapy to the skull base, and three patients had received chemoradiotherapy. On average, surgery was performed 3.9 years after chemo and/or radiotherapy termination, except for 1 patient for whom the tympanoplasty was performed during chemotherapy treatment. A retroauricular approach was used for one of the pediatric cancer patients, a transcanal approach was performed in one other and five patients benefited from an otoendoscopic approach. Tragal perichondrium with cartilage was used in most of the pediatric cancer survivor cases (four out seven cases) while xenograft (Biodesign) and Temporalis fascia without cartilage graft were used in five out of the seven control cases. Rate of tympanic membrane perforation recurrence was similar between groups (28.6%). Mean functional gain for air conduction Pure Tone Average (AC PTA) was 2.6 and 7.7 dB HL for the oncologic and control group, respectively. Mean postoperative air-bone gap (ABG) was 10.7 dB HL [median = 8.7; inter-quartile range (IQR) = 13.8] for the oncologic cohort and 10.1 dB HL (median = 10.7; IQR = 9.6) for the control group. Discussion Chemo- and chemoradiotherapy to the skull are associated with damages to the inner and middle ear structures with secondary eustachian tube dysfunction and chronic middle ear effusion. Although healing abilities and immunological defenses are compromised as part of the expected effects of antineoplastic therapies, type I tympanoplasty can be safe and effective in this population. While different approaches may be considered, otoendoscopy showed excellent results with less morbidity in this vulnerable population.